Molecular Portrait of Metastasis-Competent Circulating Tumor Cells in Colon Cancer Reveals the Crucial Role of Genes Regulating Energy Metabolism and DNA Repair. (6th January 2020) - Alix-Panabières, Catherine; Cayrefourcq, Laure; Mazard, Thibault; Maudelonde, Thierry; Assenat, Eric; Assou, Said
Abstract: BACKGROUND: Unraveling the molecular mechanisms that regulate the biology of metastasis-competent circulating tumor cells (CTCs) is urgently needed to understand metastasis formation and tumor relapse. Our group previously established the first cell line (CTC-MCC-41) derived from metastasis-competent CTCs of a patient with colon cancer. METHODS: In this study, we analyzed the transcriptome of CTC-MCC-41 cells using Human Genome U133 Plus 2.0 microarrays with the aim of unraveling the molecular basis of their special features (stem cell properties and ability to initiate and support metastasis formation). RESULTS: Comparison of the transcriptome data of metastasis-competent CTC-MCC-41 cells and of HT-29 cells (derived from a primary colon cancer) highlights the differential expression of genes that regulate energy metabolism [peroxisome proliferator-activated receptor γ coactivator 1A ( PPARGC1A ), peroxisome proliferator-activated receptor γ coactivator 1B ( PPARGC1B ), fatty acid binding protein 1 ( FABP1 ), aldehyde dehydrogenase 3 family member A1 ( ALDH3A1 )], DNA repair [BRCA1 interacting protein C-terminal helicase 1 ( BRIP1 ), Fanconi anemia complementation group B ( FANCB ), Fanconi anemia complementation group M ( FANCM )], and stemness [glutaminase 2 ( GLS2 ), cystathionine-beta-synthase ( CBS ), and cystathionine gamma-lyase ( CTH )]. The differential expression of 20 genes was validated by quantitative reverse transcription PCR. CONCLUSIONS: This study gives a comprehensive outlook on the molecular events involved in colon cancer progression and provides potential CTC biomarkers that may help develop new therapies to specifically target CTCs with stem cell properties that cause metastases and tumor relapse in patients with colon cancer.